2015
DOI: 10.1111/joms.12171
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Shareholder Democracy: A Multilevel Study of Shareholder Dissent in 15 Western European Countries

Abstract: This study develops an expressive understanding of shareholder dissent. In this view, shareholder dissent is not only about the voting outcomes of proposals put to the vote, but also expresses an evaluation of the firm's corporate governance set-up. We hypothesize that shareholder dissent expresses an agency theoretical evaluation of corporate governance, but that the degree to which the capitalist system of a country is a coordinated market economy (CME) leads shareholders to evaluate corporate governance mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 140 publications
(208 reference statements)
0
44
0
Order By: Relevance
“…CEO duality is positively associated with a higher number of shareholders' dissent votes. Previous studies such as Conyon () and Sauerwald et al () have shown that CEO duality leads to more shareholders' dissent. In addition, the log of net sales has mixed results with shareholders' dissent votes.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…CEO duality is positively associated with a higher number of shareholders' dissent votes. Previous studies such as Conyon () and Sauerwald et al () have shown that CEO duality leads to more shareholders' dissent. In addition, the log of net sales has mixed results with shareholders' dissent votes.…”
Section: Resultsmentioning
confidence: 94%
“…Although previous studies tend to show that shareholders vote with incumbent management (Armstrong, Gow, & Larcker, 2013;Conyon & Sadler, 2010;del Guercio & Hawkins, 1999;Listokin, 2010;Smith, 1996), a recent study by Sauerwald, Van Oosterhout, and Van Essen (2016) argues that shareholders' dissent can be viewed as an effective corporate governance mechanism even though it may not affect the voting outcome directly. According to some studies, shareholders are publicly making their views known with their dissent voting indicating that they are not satisfied with the present management and thereby leading to a negative evaluation of a firm's corporate governance (Hillman et al, 2011;Sauerwald et al, 2016). Previous studies identify several negative effects of dissenting shareholders on firm outcomes such as the decrease of firm value, the replacement of the CEO and of other board members, and even the takeover of the firm in the long term (for recent reviews, see Goranova & Ryan, 2014;Obermann & Velte, 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A review of past empirical research allowed considering several control variables in this analysis. The board size (BODSIZE)—in line with Sauerwald, Van Oosterhout, and Van Essen () and De Andrés, Arranz‐Aperte, and Rodríguez‐Sanz ()—was calculated as the total number of directors on boards. The second control variable was company performance, proxied with Tobin's Q (García‐Ramos, Díaz‐Díaz, & García‐Olalla, ) and denoted by Q_TOBIN.…”
Section: Empirical Designmentioning
confidence: 99%
“…Along with Solomon (2017), Moriarty (2016) and Sauerwald et al (2016) we pose premise that the existence of liberty and freedom to share opinions are very important to enforce good governance among ISSN 1948-4658 2017 not-for-profits. Public opinion must be acknowledged as insights for future improvement.…”
Section: Exploring Organizational Democracymentioning
confidence: 99%